Effect of high voltage electrical stimulation in temporomandibular disorders: a randomized controlled trial. - Arikan, Halime; Citaker, Seyit; Ucok, Cahit; Ucok, Ozlem (Physiotherapy Theory & Practice, 2025)
Objective: To examine the effects of high voltage electrical stimulation (HVES) on pain intensity, maximum mouth opening (MMO), cervical mobility, head position, pressure pain thresholds (PPTs), bite force, joint sounds, and jaw muscle strength in individuals with temporomandibular disorders (TMDs). Methods: Thirty-four individuals with TMDs were randomly divided into the exercise group (EG) (n = 17) and the HVES group (HG) (n = 17). For 4 weeks, EG received exercise therapy alone, while HG received HVES (12 sessions in total, 3 days a week to anterior temporalis and masseter) in conjunction with exercise. Results: After the treatment, in both groups, pain intensity significantly decreased (p <.001); MMO (7.27 mm in HG and 3.61 mm in EG), cervical mobility, head position, PPTs, bite force, and jaw muscle strength significantly increased (p =.043 to <.001). Joint sounds significantly decreased in the HG (p =.008). Left bite force (p =.040) and left medial pterygoid PPT (p =.013) increased more in EG. The change in left bite force in EG over time was significant (p =.040; ηp2 =.126). The effect sizes of treatments were medium to large (from.527 to 1.602) for the evaluated parameters. Conclusion: Although exercise alone was effective in many parameters evaluated, additional application of HVES provided further improvement for pain, MMO, cervical mobility, PPTs, jaw muscle strength and joint sounds. HVES can be routinely used in clinics for individuals with TMDs.